Flowering and fruiting responses to climate change of two Arctic plant species, purple saxifrage (Saxifraga oppositifolia) and mountain avens (Dryas integrifolia) - Panchen Zoe A.; Gorelick Root (Arctic Science, 2015)
In temperate regions, there are clear indications that spring flowering plants are flowering earlier due to rising temperatures of contemporary climate change. Temperatures in temperate regions are rising predominantly in spring. However, Arctic regions are seeing unprecedented temperature increases, predominantly towards the end of the growing season. We might, therefore, expect to see earlier flowering of later-season flowering Arctic plants. Parks Canada has been monitoring purple saxifrage (Saxifraga oppositifolia) and mountain avens (Dryas integrifolia) flowering and fruiting times for 20 years at Tanquary Fiord, Quttinirpaaq National Park, Ellesmere Island. Saxifraga oppositifolia flowers in early spring, while D. integrifolia flowers in midsummer. Over the 20-year period, Tanquary Fiord's annual and late-summer temperatures have risen significantly. During the same timeframe, D. integrifolia showed a trend towards earlier flowering and fruiting, but S. oppositifolia showed no changes in flowering or fruiting time. Flowering time was related to monthly temperatures just prior to flowering. The number of flowers produced was related to the previous autumn's monthly temperatures. We found no relationship between flowering time and snowmelt date. Our findings suggest that Arctic community level ecological effects from climate change induced phenology changes will differ from those in temperate regions.